Butch-femme dynamics in Exodus 2-6 and 14: A lesbian-focused character study - Focht, Caralie (Theology & Sexuality, 2019)
This article assesses Exodus’ Egypt as lesbian bar culture of the 1940s and 1950s, treating the main characters of Moses, Pharaoh, Yhwh as competing butches for the femme, Israel. The article utilizes a gender reversal, queer-ideological critical approach in order to read the biblical text of Exodus 2-6 and 14 in the way accessible to the lesbian community.
Keywords: approches et analyses; bible; discipline; genre; personnes lesbiennes; queer; ressource en ligne; science des religions; sciences humaines